An Alternative Look at History - Chan, Leandro M. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Review of the book tag Transnationalization, the State, and the People: The Philippine Case . Working papers of the United Nations University Asian Perspective Project (Southeast Asia).